THE EFFECT OF WHOLE BRAIN TEACHING METHOD TOWARD STUDENTS VOCABULARY ACHIEVEMENT OF SEVENTH GRADE AT SMP NEGERI 17 KEC. KEP. MASALOKA RAYA - Nirmala, Nirmala; Nggawu, La Ode; Fatmawati, Wa Ode (Universitas Halu Oleo, 2020)
The researcher investigated the effect of whole brain teaching method toward students vocabulary achievement at SMPN 17 Kec. Kep Masaloka Raya. The design of the research was pre-experimental design. The population of the research were all the seventh grade students of SMPN 17 Kec. Kep. Masalaoka Raya. In taking sample the researcher using purposive sampling then the researcher chose class VII A of SMPN 17 Kec. Kep. Masaloka Raya which are consist of 28 students. The research used three kinds of vocabulary instrument. The instrument were fill the blank, match word, and rearrange word. The vocabularies test consist of 10 items each test. The test complied by the researcher based on the material in English book in the seventh grade, entitled Ring of The bells. In this research, quantitative data was collected and analyzed by using paired sample t test in SPSS 16.0. the result of the analysis show that the probability value (p) was lower than alpha value (Î±) at the level significant 95% (0.000 Ë‚ 0.05). This finding result justified that there was significant differences between students vocabulary score on pretest and post-test or there was significant effect of applying whole brain teaching method toward student vocabulary achievement at seventh grade of SMPN 17 Kec. Kep. Masaloka Raya after treatment. The result prove that the hypothesis of the research was accepted H1 but H0 was rejected.